Black women diversity leaders' perceptions of organizational inclusivity in college sports - Keaton, Ajhanai Channel Inez (Frontiers in Sports and Active Living, 2022)
Select collegiate athletic departments have adopted Athletic Diversity and Inclusion Officer (ADIO) positions. ADIOs are formally tasked with the job responsibilities of creating diverse, equitable, and inclusive athletic departments and many individuals holding the position are Black men and women. This hermeneutic phenomenological study focused on the leadership of Black women in the ADIO position and examined how their racial and gender identity informed their perceptions of organizational inclusivity. Findings reveal that the intersecting identities of Black women are drawn upon and centered to make sense of what organizational inclusivity is, which are organizational contexts inclusive to Black women. More specifically, organizational inclusivity is creating contexts that do not mirror Black women’s experiences as outsiders within mostly White athletic departments, lived experiences entangled in systems of oppression, specifically sexism and racism (read: intersectionality), and experiences that cultivate Black feminist thought in Black women, as this consciousness is only developed through adverse realities of exclusion. Hence, Black women ADIOs’ perception of organizational inclusivity is informed by their own intersectional lived experiences of exclusion in sport and society writ large.